2014
DOI: 10.5114/pm.2014.43818
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and anti-inflammatory cytokine changes related to menopause

Abstract: The aim of the studyThe aim of the study was to determine menopause-related changes in serum levels of main proinflammatory and anti-inflammatory cytokines.Material and methodsThe study included 175 women, who were divided into 5 study groups (group 1 – fertile women; group 2 – pre- and perimenopausal women; group 3 – postmenopausal women; group 4 – surgically induced menopausal women; group 5 – women with chronic inflammatory pathology). We evaluated the serum levels of interleukin (IL)-1α, IL-1β, IL-2, IL-4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 26 publications
1
61
0
3
Order By: Relevance
“…Significant differences were found in vascular parameters between cases and controls like loops diameter, vessels tortuosity in labial mucosa and periodontal mucosa density was changed in view of predisposed to inflammation [18]. The ingrained studies have stated that a low systemic inflammatory status was associated with the onset of menopause and slowly the inflammatory condition increases with the downturn of hormones associated with menopause and increased serum levels of proinflammatory cytokines IL-1, IL-6, or tumor necrosis factor α in postmenopause women [19][20][21][22]. Osteopenia was more common in premenopausal women than postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences were found in vascular parameters between cases and controls like loops diameter, vessels tortuosity in labial mucosa and periodontal mucosa density was changed in view of predisposed to inflammation [18]. The ingrained studies have stated that a low systemic inflammatory status was associated with the onset of menopause and slowly the inflammatory condition increases with the downturn of hormones associated with menopause and increased serum levels of proinflammatory cytokines IL-1, IL-6, or tumor necrosis factor α in postmenopause women [19][20][21][22]. Osteopenia was more common in premenopausal women than postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Their levels correlate with a higher BMI and this significant increase in IL-8 level persist for a long period after estrogen deficiency. [59,11,60] In contradiction, Dorneles et al [61] demonstrated that high intensity interval exercise (HIIE) decreased IL-8 in lean and obese individuals. Also, Thorbjorn et al [62] founded that exercise increased IL-8 expression in skeletal muscle but small release of IL-8 from muscle not elevate plasma level of IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Given that our study population was primarily middle-aged, it is also possible that hormonal changes related to oral contraceptive use and menopause in women might influence immune responses. (45, 46)…”
Section: Discussionmentioning
confidence: 99%